Parametric Study on Responses of a Self-Anchored Suspension Bridge to Sudden Breakage of a Hanger - Wenliang Qiu; Meng Jiang; Cailiang Huang (The Scientific World Journal)
The girder of self-anchored suspension bridge is subjected to large compression force applied by main cables. So, serious damage of the girder due to breakage of hangers may cause the collapse of the whole bridge. With the time increasing, the hangers may break suddenly for their resistance capacities decrease due to corrosion. Using nonlinear static and dynamic analysis methods and adopting 3D finite element model, the responses of an actual self-anchored suspension bridge to sudden breakage of hangers are studied in this paper. The results show that the sudden breakage of a hanger causes violent vibration and large changes in internal forces of the bridge. In the process of the vibration, the maximum tension of hanger produced by breakage of a hanger exceeds 2.22 times its initial value, and the reaction forces of the bearings increase by more than 1.86 times the tension of the broken hanger. Based on the actual bridge, the influences of some factors including flexural stiffness of girder, torsion stiffness of girder, flexural stiffness of main cable, weight of girder, weight of main cable, span to sag ratio of main cable, distance of hangers, span length, and breakage time of hanger on the dynamic responses are studied in detail, and the influencing extent of the factors is presented.